Pengaruh Budaya Organisasi, Kepuasan Kerja Dan Pengendalian Intern Terhadap Kinerja Instansi Pemerintah Kota Pekanbaru - Annisa, Cahya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to look at examine empirically the effect of the influence of organizational culture , job satisfaction, internal control of the performance of government agencies in the city of Pekanbaru . This study uses primary data from the original data from the original sources by using a questionnaire. Data analysis methods used to perform hypothesis testing is multiple regression analysis. Previously conducted analysis, each variable tested the data reliability. Based on the analysis,it is know that organizational culture , job satisfaction, internal control of the performance of government agencies in the city of Pekanbaru to the coefficient of determination is 0.661 which shows the influence of the independent variables used in the model study of audit planning as the dependent variable was 66.1 % . Meanwhile , 33.9 % more changes to the audit plan is still influenced by other variables not included in this study .Keywords : Organizational Culture , Job Satisfaction , Internal Control , Agency Performance